MINAT PESERTA DALAM MENGIKUTI PENCAK SILAT PADA PERGURUAN PERSAUDARAAN SETIA HATI TERATE (PSHT) KOTA LUBUKLINGGAU - Eka Susanti; Yeni Asmara; Rais Firlando ($$8@@&&$%K, 2022)
This study aims to determine the participants' interest in participating in Pencak Silat at the Setia Hati Terate Brotherhood College (PSHT) in Lubuklinggau City. Qualitative descriptive research method. Data collection techniques in the study used observation, questionnaires (questionnaires) and interviews. The data analysis technique used in this research is descriptive qualitative analysis with percentages. The results of the analysis show that internal factors with attention indicators have 82% results or in very good criteria, happy feeling indicators have 76% results or in good criteria and activity indicators have 84% results or in very good criteria. External factors with indicators of the role of teachers / trainers have 81% results or in very good criteria, Then the facility indicators have 71% results or are in good criteria, Next, family indicators have 89% results or in very good criteria, while environmental indicators have 73 results % or in good criteria. The research showed that the participants' interest in participating in Pencak Silat at the Setia Hati Terate Brotherhood College (PHST) of Lubuklinggau City which was carried out on elementary and junior high school students had 79% results or good criteria.